Analysis of e-Invoice Automation and Internal Control in Reducing Tax Corrections in Distribution Companies in East Java - Loso Judijanto; Irwan Irawadi Barus; Kimsen Kimsen; Eko Sudarmanto; Triana Zuhrotun Aulia (West Science Social and Humanities Studies, 2026)
This study aims to analyze the effect of electronic invoice automation and internal control systems on reducing tax adjustments in distribution companies in East Java. The research adopts a quantitative approach using primary data collected from 65 respondents through structured questionnaires measured on a Likert scale. Data analysis was conducted using IBM SPSS Statistics version 25, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that electronic invoice automation has a significant negative effect on tax adjustments, indicating that the implementation of automated systems improves accuracy and minimizes discrepancies in tax reporting. Internal control systems also demonstrate a significant negative influence on tax adjustments, highlighting their role in ensuring compliance, preventing errors, and strengthening financial reporting processes. Simultaneously, both variables significantly affect tax adjustments, suggesting that the integration of digital systems and effective control mechanisms enhances overall tax compliance. The coefficient of determination indicates that 57.9% of the variation in tax adjustments can be explained by electronic invoice automation and internal control systems. This finding emphasizes the importance of combining technological innovation with organizational governance to reduce fiscal risks. The study contributes to the literature by providing empirical evidence on the effectiveness of digital taxation systems and internal controls, and offers practical implications for companies and policymakers in improving tax compliance and operational efficiency.